Cooperativity between far upstream enhancer and proximal promoter elements of the human {alpha}2(I) collagen (COL1A2) gene instructs tissue specificity in transgenic mice. - Tanaka, S; Antoniv, T; Liu, K; Wang, L; Wells, D; Ramirez, F; Bou-Gharios, G (2004)
Interaction between the proximal (-378) promoter and the far upstream (-20 kb) enhancer is essential for tissue-specific expression of the human alpha2(I) collagen gene (COL1A2) in transgenic mice. Previous in vitro studies have shown that three Sp1 binding sites (around -300) are part of a cytokine-responsive element and that two TC-rich boxes (around -160 and -125) and a CBF/NFY consensus sequence (around -80) confer optimal promoter activity by interacting among themselves and with the upstream Sp1 sites. Here we report that mutations of the Sp1 binding sites, TC-rich boxes or CBF/NFY consensus sequence lead to reduced transgene activity, thus underscoring the functional interdependence of the proximal promoter elements. Loss of the Sp1 binding sites was associated with loss of transgene expression in osteoblasts, whereas elimination of the CBF/NFY binding site (alone or in combination with the TC-rich boxes) was correlated with a lack of activity in the ventral fascia and head dermis and musculature. Additionally, transgene expression in skin fascia fibroblasts depended on the integrity of the Sp1 binding sites and TC-rich boxes, and on their physical configuration. Evidence is also presented suggesting cooperativity between cis-acting elements of the far upstream enhancer and proximal promoter in assembling tissue-specific protein complexes. This study thus reiterates the complex and highly combinatorial nature of the regulatory network governing COL1A2 transcription in vivo.